2021
DOI: 10.1111/cdev.13662
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocortical and psychosocial responses of families in Jordan to the COVID‐19 pandemic

Abstract: This study of 52 predominantly lower income Jordanian and Syrian families with young children (31 girls; M age = 53.37 months, SD = 3.53) in Jordan began in 2019, before the pandemic. Families were followed to explore stress physiology, family functioning, and mental health over the first 9 months of the pandemic. Mothers reported less adaptive coping and more negative changes to family life in June 2020 when their children had poorer behavioral self-regulation and more behavior problems, and when families had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…Hastings et al ( 2021 ) leveraged data from an ongoing study on low‐income families in Jordan to investigate stress physiology and family functioning during the first 9 months of the pandemic. Researchers guided mothers on how to obtain hair samples from themselves and their children.…”
Section: The Special Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hastings et al ( 2021 ) leveraged data from an ongoing study on low‐income families in Jordan to investigate stress physiology and family functioning during the first 9 months of the pandemic. Researchers guided mothers on how to obtain hair samples from themselves and their children.…”
Section: The Special Sectionmentioning
confidence: 99%
“…Receipt of supplementary nutrition was associated with decreases in child and caregiver food insecurity and a decrease in indicators of parental depression. Hastings et al (2021) leveraged data from an ongoing study on low-income families in Jordan to investigate stress physiology and family functioning during the first 9 months of the pandemic. Researchers guided mothers on how to obtain hair samples from themselves and their children.…”
Section: Food Insecuritymentioning
confidence: 99%
“…In Eales, Gillespie, Alstate, Ferguson, and Carlson ( 2021 ), children with behavior problems engaged in more problematic media use during the pandemic. Hasting and colleagues (Hastings, Partington, Dajani, & von Suchodoletz, 2021 ) found that among low‐income families in Jordan, children who pre‐pandemic scored more poorly on an executive function task, had families who were described as experiencing more negative changes in response to the pandemic.…”
Section: Self Regulation and Prosocial Behaviormentioning
confidence: 99%
“…As COVID-19 continues and new variants arise, and evidence mounts for the adverse effects of pandemic living conditions on children’s mental health ( Bignardi et al, 2021 ; Creswell et al, 2021 ), there is growing need to examine the factors that may buttress children’s well-being and healthy adjustment ( Wade et al, 2020 ). Effective family functioning during the first few weeks of shelter-in-place has been associated with children’s concurrent positive adjustment ( Chu et al, 2021 ; McArthur et al, 2021 ), with benefits for children’s adjustment potentially persisting for several months ( Hastings et al, 2021 ). How families initially responded to and coped with COVID-19 may have had persisting influences on children’s emotional and behavioral trajectories as the pandemic continued.…”
Section: Introductionmentioning
confidence: 99%